Modelling and fuzzy controlling of lung mechanics - Güler, Hasan; Türko?lu, Ibrahim (My University, 2010)
In this study, simulation and control of lung mechanic were implemented by using of fuzzy logic. Since respiration system has complex structures, it is important to model lung truely. Basically, lung can be represented by three different forms. These are single compartment model, series two compartment model and parallel two compartment model. In this study, simulation of the respiration system was implemeted by using these models. Respiration time was determined with fuzzy logic. Fuzzy logic has two inputs. These are the error Pe(k) between reference pressure value (Pref) and pressure of gas given sick person (Phasta) and error change rate ?Pe(k) were considered. Performed system is run with the pressure control ventilation (PCV) which is one of the most used modes among other ventilation modes.
Akci?er mekani?inin modellenmesi ve bulanik kontrolü
2010 7th National Conference on Electrical, Electronics and Computer Engineering, ELECO 2010 -- 2 December 2010 through 5 December 2010 -- Bursa -- 83834
Keywords: Biological organs; Computer simulation; Electrical engineering; Fuzzy systems; Mechanics; Compartment model; Complex structure; Lung mechanics; Pressure values; Two-compartment models; Ventilation mode; Fuzzy logic